Monitoring and analysis of low-voltage network with smart grid architecture model by developing use cases - Kumar, Haresh; Kumar, Jagdesh; Devi, Jherna (Sciendo, 2021)
The objective of this paper is to show the characteristics of smart meters enabling to monitor and analyze the low-voltage (LV) network. This is achieved by developing use cases, where power quality and outage data are transferred from smart meters through distribution network to the control center. To visualize the monitoring process of LV network, the use cases are mapped into smart grid architecture model. The paper proposes a solution to analyze the LV network interruption and power quality problems (over-voltage, under-voltage, voltage sags, and swells). Thus, this paper provides a smart platform for monitoring LV network.
Keywords: Advanced metering infrastructure; Outage management; Power quality monitoring; Use cases; Smart grid architecture model; fi=Sähkötekniikka|en=Electrical Engineering|